Enhancing early attachments theory, research, intervention, and policy - Berlin, Lisa J.; Ziv, Yair; Jackson, Lisa Amaya; Greenberg, Mark T. (The Guilford Press, 2005)
"Recent years have seen the development of myriad intervention programs focusing on child-parent attachments, but which ones really work? Can the neurological sequelae of disrupted attachments be reversed? How do early attachment-related services fit into today's policy agenda? This authoritative volume synthesizes the latest knowledge in this crucial area and offers a unique overview of evidence-based treatment and prevention approaches currently in use. With contributions from leaders in the field, the book highlights how scientifically informed services can make a lasting difference in the lives of vulnerable children and families."--BOOK JACKET